2021
DOI: 10.1126/sciadv.aba1180
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neocortex arealization and Sotos-like syndrome–associated behavior in Setd2 mutant mice

Abstract: Proper formation of area identities of the cerebral cortex is crucial for cognitive functions and social behaviors of the brain. It remains largely unknown whether epigenetic mechanisms, including histone methylation, regulate cortical arealization. Here, we removed SETD2, the methyltransferase for histone 3 lysine-36 trimethylation (H3K36me3), in the developing dorsal forebrain in mice and showed that Setd2 is required for proper cortical arealization and the formation of cortico-thalamo-cortical circuits. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…It is thus conceivable that FGF signaling and Nr2f1 might act together as upstream regulators of a cascade of molecular events governing area patterning, whereas other genes such as Pax6 and Emx2 would act either as secondary downstream effectors or in parallel pathways and have a weaker effect on arealization. Finally, several chromatin regulators, such as the methyl-transferase Setd2 (Xu et al, 2021 ), the transcription co-regulator Cited2 (Fame et al, 2016 ; Wagner and MacDonald, 2021 ) and the epigenetic co-factor LIM Domain Only-4 ( Lmo4 ; Harb et al, 2016 ), have been reported to influence area identity refinement. Considering Nr2f1 ability to recruit epigenetic factors (Montemayor et al, 2010 ), it might be interesting to investigate whether these or similar chromatin regulators act in association with or under the control of Nr2f1 in the late arealization process.…”
Section: Nr2f1 Specifies the Identity Of Posterior Sensory Areasmentioning
confidence: 99%
“…It is thus conceivable that FGF signaling and Nr2f1 might act together as upstream regulators of a cascade of molecular events governing area patterning, whereas other genes such as Pax6 and Emx2 would act either as secondary downstream effectors or in parallel pathways and have a weaker effect on arealization. Finally, several chromatin regulators, such as the methyl-transferase Setd2 (Xu et al, 2021 ), the transcription co-regulator Cited2 (Fame et al, 2016 ; Wagner and MacDonald, 2021 ) and the epigenetic co-factor LIM Domain Only-4 ( Lmo4 ; Harb et al, 2016 ), have been reported to influence area identity refinement. Considering Nr2f1 ability to recruit epigenetic factors (Montemayor et al, 2010 ), it might be interesting to investigate whether these or similar chromatin regulators act in association with or under the control of Nr2f1 in the late arealization process.…”
Section: Nr2f1 Specifies the Identity Of Posterior Sensory Areasmentioning
confidence: 99%
“…However, only deficits in H2A.Z lead to dendritic arborization defects (Shen et al, 2018). Together deficits in NPC proliferation, neuronal differentiation, and arborization could contribute to the defects in arealization and the aberrant thalamo-cortical circuits associated with loss of Setd2 (Xu et al, 2021). Therefore, we posit that the modulation of the chromatin environment by SETD2 plays an important role in the regulation of cell fate transitions during neurogenesis, and the structural development of neuronal circuits.…”
Section: Setd2 Gain or Loss Of Function Differentially Impact Brain Sizementioning
confidence: 92%
“…Hence cell specific knockout studies will be important to define cell-type specific mechanisms governed by SETD2 during the development of neuronal circuitry. In fact, knockout of Setd2 in the developing forebrain revealed abnormal cortical arealization and aberrant thalamo-cortico-thalamic circuits in mice that also had defects in social interaction, motor learning and spatial memory (Xu et al, 2021). The observed neural phenotypes associated with SETD2 dysfunction could be related in part to changes in the chromatin environment.…”
Section: Setd2 Gain or Loss Of Function Differentially Impact Brain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…All sections were counterstained with 4′,6‐diamidino‐2‐phenylindole dihydrochloride (DAPI, B2261; Sigma–Aldrich). The primary antibody used was rat anti‐BrdU (1:1000, ab6326; Abcam, Cambridge, UK) [Hewitt et al, 2021; Xu et al, 2021]. The fluorescent secondary antibody used was donkey anti‐rat Alexa Fluor 488 (1:500, A21208; Invitrogen, Carlsbad, CA) [Yang et al, 2016].…”
Section: Methodsmentioning
confidence: 99%